A device review of Relivion®: an external combined occipital and trigeminal neurostimulation (eCOT-NS) system for self-administered treatment of migraine and major depressive disorder. (3rd April 2021) - Daniel, Oved; Sharon, Roni; Tepper, Stewart J.
ABSTRACT: Introduction : Many patients with migraine are non-responsive or intolerant to pharmaceutical or surgical interventions. Peripheral nerve stimulation (PNS) offers a potential solution for these patients. This review discusses the external combined occipital and trigeminal neurostimulation (eCOT-NS) provided by the Relivion®, a multi-channel head-mounted device for self-administered PNS. Areas covered : Challenges and advantages of PNS systems for the treatment of migraine and depression are introduced, followed by an overall review of clinical evidence of the efficacy of the Relivion® system in treating migraine. The supporting smartphone app and cloud-based analytics which enable remote treatment management by the health care provider are also discussed. Recent empirical indications for the potency of this PNS combination for the treatment of depression are also summarized. Expert opinion : Relivion® is an eCOT-NS system, featuring Food and Drug Administration-approved, noninvasive, self-administered, customizable, multi-focal PNS for the treatment of migraine. In accordance with current telehealth trends, the Relivion® also enhances remote disease management and personalization using digital-monitoring, cloud-based technology, and artificial intelligence. As research on this system progresses, it may become the preferred treatment for the management of a number of neurological and psychiatric diseases, with migraine and major depressive disorders as precedents.